An Analysis of Monitoring and Control Technologies Used in Construction Companies in Sultanate of Oman - KHALFAN, ISSA; SAID, SULAIMAN; JAMALUDDIN, ZAHARUZAMAN; WIDYARTO, SETYAWAN (The journal of contemporary issues in business and government, 2021)
Monitoring and control is an essential process in construction project management and delivery. It is therefore imperative for construction companies to employ the use of the most effective monitoring and control techniques available to meet project objectives. Nowadays, innovative information technology is used to optimize project management, which has a strong ability to indicate and control project activities throughout the project life cycle by using project software and utilizing this type of software to manage and develop the formalization level of project management to ensure the project is free of quality, cost, time issues, accident prevention, and other issues. As a result, the failure to use monitoring and control technologies while constructing the project has resulted in the failure of many projects and dissatisfaction with the project. Consequently, it may deliver the project with low quality and over planning budget and also exceed the target day. The goal of this research is to evaluate monitoring and control technologies used in construction projects in the Sultanate of Oman and to make recommendations for improving monitoring and control technologies and software programs in construction projects in the Sultanate of Oman. In the Sultanate of Oman, a research project was conducted using the questionnaire approach in 33 construction industries. The measurement and model reliability and validity were assessed using confirmatory factor analysis. Lastly, the conclusion has been added to aid construction firms and the project. Academically, this research contributes to students’ and employees’ expertise, as well as providing a breakthrough for practitioners in understanding the core functions of variables in the construction industry.